Optical coherence tomography of the Tokay gecko (Gekko gecko) eye. (2nd August 2020) - Go, Seokmin; Kang, Seonmi; Kwon, Jun; Park, Sechang; Seo, Kangmoon
Abstract: Objective: To provide images of the anterior and posterior structures of the gecko eye using spectral domain optical coherence tomography (SD‐OCT). Animals and procedures: Eight ophthalmologically normal Tokay geckos ( Gekko gecko ) were used. The nose‐cloaca distance and body weight were measured for each gecko. Tomographic images were obtained using SD‐OCT without the use of anesthetic or mydriatic agents. The central corneal thickness (CCT), the anterior chamber depth (ACD), and the length of the conus papillaris (CP) were manually measured using OCT images. The thickness of the retinal nerve fiber layer (RNFL) around the CP and the retinal thickness in all four quadrants (superior, nasal, inferior, and temporal areas) were automatically measured using the OCT software program. Results: The mean values of the nose‐cloaca distance and body weight were 13.8 ± 0.9 cm and 41.3 ± 9.0 g, respectively. The mean values of CCT, ACD, and CP length were 177.6 ± 20.9 µm, 1205.0 ± 79.9 µm, and 1546.4 ± 208.8 µm, respectively. The mean value of RNFL thickness was 52.0 ± 8.2 µm, and the superior region was the thickest. The mean value of total retinal thickness was 202.5 ± 9.4 µm, and the temporal region was the thickest. Conclusions: Tomographic images of the anterior and posterior segments of the living gecko eye could be obtained using the OCT unit. Multiple retinal layers and anatomical features of the CP were identified.